Handling of Files on Mini-Computers - Echallier, J. F.; Laviron, A.; Peronnet, F.; Gehin, P. (Methods of Information in Medicine, 1972)
This paper describes a programme for bibliographical, medical and other files. It is run on a mrnicomputer with 4 K words of 12 bits each and with external storage on magnetic tape.After the data has been stored, a series of checks is systematically carried through in order to keep the file reliable.Logic relations (»and«, »or«, »except«) of characteristics of a record can be combined for searching purposes.As a rule, computers made for and bought by laboratories are used for processing laboratory data; the programme described here permits an interesting additional application: the handling of files of bibliographical or other textual information.
Keywords: Bibliographical Data; Filehandling; Information Storage and Retrieval; Mini-Computers